Brain Control of Plasma Cholesterol Involves Polysialic Acid Molecules in the Hypothalamus - Brenachot, Xavier; Gautier, Thomas; Nédélec, Emmanuelle; Deckert, Valérie; Laderrière, Amélie; Nuzzaci, Danaé; Rigault, Caroline; Lemoine, Aleth; Pénicaud, Luc; Lagrost, Laurent; Benani, Alexandre (Frontiers in Neuroscience, 2017)
The polysialic acid (PSA) is a large glycan that is added to cell-surface proteins during their post-translational maturation. In the brain, PSA modulates distances between cells and controls the plasticity of the nervous system. In the hypothalamus, PSA is involved in many aspects of energy balance including food intake, osmoregulation, circadian rhythm and sleep. In this work, we investigated the role of hypothalamic PSA in the regulation of plasma cholesterol levels and distribution. We report that HFD consumption in mice rapidly increased plasma cholesterol, including VLDL, LDL and HDL-cholesterol. Although plasma VLDL-cholesterol was normalized within the first week, LDL and HDL were still elevated after 2 weeks upon HFD. Importantly, we found that hypothalamic PSA removal aggravated LDL elevation and reduced HDL levels upon HFD. These results indicate that hypothalamic PSA controls plasma lipoprotein profile by circumventing the rise of LDL-to-HDL cholesterol ratio in plasma during overfeeding. Although mechanisms by which hypothalamic PSA controls plasma cholesterol homeostasis remains to be elucidated, these findings also suggest that low level of hypothalamic PSA might be a risk factor for dyslipidemia and cardiovascular diseases.